Structural mechanism of ligand activation in human calcium-sensing receptor - Geng, Yong (eLife, 2016)
Human calcium-sensing receptor (CaSR) is a G-protein-coupled receptor (GPCR) that maintains extracellular Ca(2+) homeostasis through the regulation of parathyroid hormone secretion. It functions as a disulfide-tethered homodimer composed of three main domains, the Venus Flytrap module, cysteine-rich domain, and seven-helix transmembrane region. Here, we present the crystal structures of the entire extracellular domain of CaSR in the resting and active conformations. We provide direct evidence that L-amino acids are agonists of the receptor. In the active structure, L-Trp occupies the orthosteric agonist-binding site at the interdomain cleft and is primarily responsible for inducing extracellular domain closure to initiate receptor activation. Our structures reveal multiple binding sites for Ca(2+) and PO(4)(3-) ions. Both ions are crucial for structural integrity of the receptor. While Ca(2+) ions stabilize the active state, PO(4)(3-) ions reinforce the inactive conformation. The activation mechanism of CaSR involves the formation of a novel dimer interface between subunits. DOI: http://dx.doi.org/10.7554/eLife.13662.001